Synthesis and herbicidal evaluation of N-cinnamoyl-N-substituted hydroxylamine and its derivatives - Kumar, Ajay; Arya, Sushila; Chandra, Sonakshi; Kotnala, Shreya; Goswami, Archana (Revista Brasileira de Engenharia de Biossistemas, 2025)
The group of cinnamon and hydroxylamine produces significant results in the field of agriculture. So, the combination of both groups in the compound performs effective results in numerous fields of the medicinal and chemical industry. Still, this type of moiety combination is not used in the agricultural field as an herbicide. The cost-effective plant that grows alongside crops develops resistance to current herbicides. To effectively combat undesirable herbs, new or modified groupings are needed. To investigate the prospect of discovering a new class of herbicide, the current work aims to synthesize derivatives of cinnamon hydroxamic acid and screen them for herbicidal activity. A cinnamo hydroxamic acid derivative was synthesized by a reaction of substituted cinnamic acids and hydroxylamine derivatives, and the final product was characterized by FTIR, 1H NMR, and 13C NMR spectroscopy. The final product was tested for herbicidal activity against Radish (Raphanus sativus) seeds at 50, 100 and 200 ppm concentrations and compared with standard pendimethalin. Amongst the tested compounds, 3-nitro cinnamo hydroxamic acid (A2), o-tolyl-(3-bromo) cinnamo hydroxamic acid (B1) and 2-bromo-(4-chloro) cinnamo hydroxamic acid) (C1) exhibited activity at par with standard pendimethalin at a concentration of 200 ppm and In silico PASS studies also showed that it has excellent herbicidal properties.